Análisis de la situación económica y financiera de la empresa Electro Oriente S.A., periodo 2020 - 2021 - Alvarado Ramos, Jhony (2022)
Every company has the responsibility to submit the economic and financial information of a given period to a permanent evaluation, in order to be able to know and understand its real situational status, and by virtue of this, the Management is capable of adopting the pertinent measures aimed at improving administrative and financial management, in such a way that I was able to obtain the best results. The present investigation is entitled "Analysis of the Economic and Financial situation of the company Electro Oriente SA, period 2020 – 2021”, it aims to determine its economic and financial situation. Its approach corresponds to a quantitative type of research and its design is descriptive, non-experimental – cross-sectional. From the analysis and discussion of the results, it was determine that the economic and financial situation of the company is positive in both periods.